2019
DOI: 10.1016/j.cub.2019.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Plasticity Drives Visual Habituation Learning in Larval Zebrafish

Abstract: Highlights d High-throughput behavioral analysis of dark-flash habituation in larval zebrafish d Multiple components of the response adapt with different habituation kinetics d Controlled by multiple circuit loci with different molecular requirements d Modular habituation selectively tunes behavioral components based on context

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
97
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 33 publications
13
97
2
Order By: Relevance
“…Series of recent studies highlight the increasing popularity of zebrafish for studying diverse aspects of animal behavior [30][31][32][33][34][35][36][37][38][39], including the more complex behaviors such as learning [25,26,[40][41][42][43][44][45][46] and social behaviors [47,48]. While studying complex behaviors in adult zebrafish allow investigation of brain function in a fully mature brain, larval and juvenile zebrafish has the tremendous advantage of a small and transparent brain, when it comes to studying brain A B C1 T1 C2 T2 T3 C3 T4 C4 T5 T6 control dHb activity [33,38,[49][50][51][52][53][54][55][56][57][58]. Hence, we investigated the ontogeny of a complex operant behavior, namely CPA learning, and showed that the learning performance of young zebrafish improves across development.…”
Section: Discussionmentioning
confidence: 99%
“…Series of recent studies highlight the increasing popularity of zebrafish for studying diverse aspects of animal behavior [30][31][32][33][34][35][36][37][38][39], including the more complex behaviors such as learning [25,26,[40][41][42][43][44][45][46] and social behaviors [47,48]. While studying complex behaviors in adult zebrafish allow investigation of brain function in a fully mature brain, larval and juvenile zebrafish has the tremendous advantage of a small and transparent brain, when it comes to studying brain A B C1 T1 C2 T2 T3 C3 T4 C4 T5 T6 control dHb activity [33,38,[49][50][51][52][53][54][55][56][57][58]. Hence, we investigated the ontogeny of a complex operant behavior, namely CPA learning, and showed that the learning performance of young zebrafish improves across development.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations that flies initially reacted to vibration with vigorous locomotion and that they can be awakened with salient changes in the visual environment also confirm that VIS is unrelated to other types of suppressed locomotion such as that induced by wind or fear in flies (Gibson et al, 2015;Yorozu et al, 2009) or tonic immobility in birds (Gallup, 1977). The habituation model of how sensory stimulation promotes sleep proposes that habituation to repetitive, unimportant stimuli leads to reduced arousal (Pavlov, 1927;Sokolov, 1963;Bohlin, 1971 (Flavell et al, 2013;McDiarmid et al, 2019;Randlett et al, 2019). These findings led to a recent proposal that habituation is more than simply learning to ignore and that it allows organisms to switch between alternative behaviors depending on the Hz stimulation may promote sleep in part through the synchronization mechanism.…”
Section: Discussionmentioning
confidence: 92%
“…For example, we quantified multiple features of habituation as we have previously shown that they habituate to different extents and with different time courses (Figure 1F-I) and because there is growing evidence that different components of a single habituating response are mediated by different molecular mechanisms. 61,79,80 Systematic quantification of the pairwise correlation between all possible phenotypic feature pairs revealed expected moderate correlations (e.g. between length and width) and clustering that reflected the feature categories we predefined ( Figure 1K).…”
Section: Asd-associated Genes Are Highly Conserved To C Elegansmentioning
confidence: 89%